Prospects of Nanobiomaterials for Biosensing - Ravindra P. Singh (International Journal of Electrochemistry)
Progress and development in biosensor development will inevitably focus upon the technology of the nanomaterials that offer promise to solve the biocompatibility and biofouling problems. The biosensors using smart nanomaterials have applications for rapid, specific, sensitive, inexpensive, in-field, on-line and/or real-time detection of pesticides, antibiotics, pathogens, toxins, proteins, microbes, plants, animals, foods, soil, air, and water. Thus, biosensors are excellent analytical tools for pollution monitoring, by which implementation of legislative provisions to safeguard our biosphere could be made effectively plausible. The current trends and challenges with nanomaterials for various applications will have focus biosensor development and miniaturization. All these growing areas will have a remarkable influence on the development of new ultrasensitive biosensing devices to resolve the severe pollution problems in the future that not only challenges the human health but also affects adversely other various comforts to living entities. This review paper summarizes recent progress in the development of biosensors by integrating functional biomolecules with different types of nanomaterials, including metallic nanoparticles, semiconductor nanoparticles, magnetic nanoparticles, inorganic/organic hybrid, dendrimers, and carbon nanotubes/graphene.